The Association between Social Isolation and Physical Activity among Korean Adolescents - Sarang Jang; Na-Young Park (MDPI AG, 2024)
Objectives: This study investigated the impact of structural isolation within peer relationships on physical activity levels among Korean adolescents, exploring how different types of social isolation within classroom networks influence physical activity. Methods: This study utilized cross-sectional survey data. Specifically, using data from the 8th Korean Children and Youth Happiness Index survey (2016), which included 3356 middle and high school students in Korea, the study employed binary logistic regression and social network analysis to assess the relationship between social isolation and physical activity. Based on types of isolation, adolescents were categorized into social avoidant, actively isolated and socially indifferent groups. Results: The analysis demonstrated significant differences in physical activity based on social isolation status (χ2 = 13.0, p < 0.001) and types of social isolation (χ2 = 18.3, p < 0.001). Key variables such as gender, household subjective economic status, and self-rated health significantly influenced physical activity. The number of physically active friends had a considerable impact on both non-isolated groups (OR = 1.31, p < 0.001) and the actively isolated group (OR = 1.42, p < 0.05). The actively isolated group exhibited the highest explanatory power in the logistic regression models (Nagelkerke R² = 0.230). Conclusions: This study has highlighted that not only social isolation but also the type of isolation significantly influences physical activity among adolescents. Understanding these distinctions and tailoring interventions accordingly are crucial for promoting physical activity among socially isolated adolescents.